Democratic transitions and episcopates in Colombia and Venezuela (1957-1959) (Quinto Sol, 2025)
Between 1957 and 1959, a critical juncture developed in Colombia and Venezuela, beginning with the collapse of dictatorships and culminating in the establishment of restricted democratic systems. This article compares the trajectories of the episcopates of both countries, arguing that the Catholic hierarchies coincided in taking distance from the governments of Rojas Pinilla in Colombia and Pérez Jiménez in Venezuela, incorporating pro-democratic civil coalitions for the overthrow of authoritarian regimes and supporting the partisan pacts that created a new political system. In the years leading up to the Second Vatican Council, the bishops of two neighboring but different churches established a new interaction with the state, which led to a reassessment of the political influence of the religious institution. This analysis draws on concepts from historical institutionalism, such as antecedents and critical junctures, change, agency, and trajectories of dependency.
Keywords: Dictatorship; Democracy; Episcopate; Political crisis